2022
DOI: 10.3390/photonics9070496
|View full text |Cite
|
Sign up to set email alerts
|

Product of Two Laguerre–Gaussian Beams

Abstract: We show that a product of two Laguerre–Gaussian (pLG) beams can be expressed as a finite superposition of conventional LG beams with particular coefficients. Based on such an approach, an explicit relationship is derived for the complex amplitude of pLG beams in the Fresnel diffraction zone. Two identical LG beams of the duet produce a particular case of a “squared” Fourier-invariant LG beam, termed as an (LG)2 beam. For a particular case of pLG beams described by Laguerre polynomials with azimuthal numbers n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Reference [11] proposed the concept of photon orbital angular momentum and proved that there is a spatial phase term in Laguerre-Gaussian beams 𝑒 𝑗𝑙𝜑 , corresponding to the OAM, and the corresponding value is lℏ. The light field distribution of a typical Laguerre-Gaussian beam can be expressed as:…”
Section: Theoretical Basis Of Vortex Em Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference [11] proposed the concept of photon orbital angular momentum and proved that there is a spatial phase term in Laguerre-Gaussian beams 𝑒 𝑗𝑙𝜑 , corresponding to the OAM, and the corresponding value is lℏ. The light field distribution of a typical Laguerre-Gaussian beam can be expressed as:…”
Section: Theoretical Basis Of Vortex Em Wavesmentioning
confidence: 99%
“…References [4][5] proposed and developed concepts such as phase dislocation, phase singularity, and vortex beam, and then conducted further research [6][7][8][9][10], gradually enriching the theory, generation, and related properties of vortex light. Reference [11] found that the vortex laser beam formed by Laguerre-Gauss (LG) beams had orbital angular momentum, and clearly determined the relationship between orbital angular momentum and vortex topological charge the relationship between. Since then, several research groups have worked on various optical vortex generation schemes [12][13][14][15][16], optical vortex manipulation of micro-nano particles [17][18][19][20][21], vortex optical micromachining [22], photon orbital angular momentum quantum entanglement properties [23][24][25], optical vortex propagation properties [26][27] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, by setting the absolute part A2 to be spatially uniform, we see that the generated field MG(2n)=M1n, meaning that in this case the generated field is a positive integer power of the signal field. For the case of spatial transverse modes, such as LG and Hermite–Gaussian beams, these fields can be seen as multiple products of modes, for which there are one-to-one correspondences 15 , 76 , 77 that essentially map the resulting field back to the original message unambiguously. In addition, this nonlinear dependence has been shown to be advantageous in detection processes 25 …”
Section: Appendixmentioning
confidence: 99%
“…In our works [ 27 , 28 ], we considered double Laguerre–Gaussian (dLG) beams and square LG beams. Both of these types of beams can be expressed via finite sums of LG beams.…”
Section: Square Bessel–gaussian Beamsmentioning
confidence: 99%
“…This leads to the qualitative difference between the Laguerre–Gaussian and the Bessel–Gaussian beams—the former have a finite number of rings, and the latter have an infinite number of rings. A natural continuation of the works [ 27 , 28 ] is the investigation of whether similar solutions to the Helmholtz equation can be obtained that describe square BG beams or the products of the BG beams.…”
Section: Square Bessel–gaussian Beamsmentioning
confidence: 99%